Eudrilus eugeniae A Potent Bioremediator in Controlling Herbicide and Pesticide Pollution - S Umamaheswari, Dr (International Journal of Pharmaceutical & Biological Archive, 2015)
Eudrilus eugeniae A Potent Bioremediator in Controlling Herbicide and Pesticide Pollution